2014
DOI: 10.1097/aln.0000000000000101
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Acupuncture–Electroacupuncture on Persistent Pain

Abstract: In the last decade, preclinical investigations of electroacupuncture mechanisms on persistent tissue-injury (inflammatory), nerve-injury (neuropathic), cancer, and visceral pain have increased. These studies show that electroacupuncture activates the nervous system differently in health than in pain conditions, alleviates both sensory and affective inflammatory pain, and inhibits inflammatory and neuropathic pain more effectively at 2–10 Hz than at 100 Hz. Electroacupuncture blocks pain by activating a variety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
465
0
21

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 620 publications
(529 citation statements)
references
References 198 publications
(237 reference statements)
5
465
0
21
Order By: Relevance
“…Ahsin et al reported a significant increase in plasma β-endorphin levels after EDN to local points at the knee that correlated with reductions in pain, stiffness and disability, which is likely due to vasodilation [144]. EDN further blocks the local release of IL-1 β and TNF-α in the synovia of osteoarthritic joints [145] and the systemic release of IL-1 β and TNF-α by inhibiting melanocortin-4 in the periaqueductal gray of the brain stem [146]. Third, there is limited evidence suggesting that DN may stimulate an increase in hyaluronic acid, allowing the synovial fluid to better lubricate the joint [147].…”
Section: Electro-dry Needling For Joint Osteoarthritis: Underlying Mementioning
confidence: 99%
See 1 more Smart Citation
“…Ahsin et al reported a significant increase in plasma β-endorphin levels after EDN to local points at the knee that correlated with reductions in pain, stiffness and disability, which is likely due to vasodilation [144]. EDN further blocks the local release of IL-1 β and TNF-α in the synovia of osteoarthritic joints [145] and the systemic release of IL-1 β and TNF-α by inhibiting melanocortin-4 in the periaqueductal gray of the brain stem [146]. Third, there is limited evidence suggesting that DN may stimulate an increase in hyaluronic acid, allowing the synovial fluid to better lubricate the joint [147].…”
Section: Electro-dry Needling For Joint Osteoarthritis: Underlying Mementioning
confidence: 99%
“…Importantly, CRH has also been shown to directly stimulate opioids release from immune cells, and CRH antagonists have been shown to block EDN's ability to inhibit pain in inflammatory tissue [156]. Corticosterone locally inhibits inflammatory cytokines, prostaglandin and cox-2, thereby optimizing opioid-based pain reduction [146,151,154]. The CRH-POMCcorticosteroid axis provides another mechanism by which EDN may be able to have an effect peripherally via non-neural cells and may further explain the positive effects of superficial DN.…”
Section: Corticotrophin Releasing Hormone Proopiomelanocortin Corticomentioning
confidence: 99%
“…Electroacupuncture stimulates Aβ fibers and modulates Nucleus Rafe Magnus (NRM) to produce analgesia. Acupuncture exerts an effect through central and peripheral mechanisms evidenced by both experimental of human and animal studies and also involves various bioactive chemicals or mediators as shown in Figure 4 [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…13 Acupuncture combined with non-narcotic analgesics may obviate the need for opioid therapy and reduce side effects associated with higher dosages of medication. 14 Assertions in recently performed literature reviews suggest that acupuncture may be effective for peripheral joint osteoarthritis, neck pain, tension-type headaches, migraine prophylaxis, and labour pain ( Table 2). For example, in 2011, Lee and Ernst published an analysis of Cochrane reviews that thoroughly addresses the specific evidence on acupuncture for pain.…”
Section: Categories Of Complementary and Alternative Medicinementioning
confidence: 99%
“…73 Despite controversy over a lack of adequate blinding and potential intellectual biases against acupuncture and other complementary therapies, evidence exists to support these therapies even at the mechanistic level. 14,[74][75][76] For example, several animal models have shown a therapeutic effect for acupuncture and other CAM therapies. Furthermore, since animals likely do not understand the difference between true vs sham therapies, we can infer that they are not likely to exhibit a placebo response.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%